Răspunsuri

2014-06-02T18:20:08+03:00


1.a)7x=14+0
x=14
x=14/7
x=2

b)4x=0-12
4x=-12
x=-12/4
x=-3

c)-9x=-27
x=-27/-9
x=3

d)-4x=36
x=36/-4
x=-9

e)2x=-10-4
2x=-14
x=-14/2
x=-7

f)10+4=7x
14=7x
14/7=x
2=x

g)6+2=4x
8=4x
8/4=x
2=x

h)-7-1=4x
-8=4x
-8/4=x
-2=x

i)11-3=2x
8=2x
8/2=x
4=x

j)5x=20
x=20/5
x=4

k)5x=10
x=1-/5
x=2

l)4x=-16
x=-16/4
x=-4

m)5x=15
x=15/5
x=3

n)-6x=-12
x=-12/-6
x-2

o)8x=-8
x=-8/8
x=-1

q)-3x=-9
x=-9/-3
x=3

r)2x=-6
x=-6/2
x=-3

2.a)5x-3x=11+3
2x=14
x=14/2
x=7

b)-2x+3x=9-15
x=-6

c)4x-3x=15-13
x=2

d)-17x+16x=43-9
-x=34
x=-34





2014-06-02T18:41:59+03:00
1. 7x-5=3x+11
7x-3x=11+5
4x=16⇒ x=16:4=4
2. 3(x-2)+10=x+24
   3x-6+10=x+24
    2x=24+6- 10=20 ⇒ x=20:2=10
3. 7(x-3)+14=32-6x
   7x-21+14=32-6x
   7x-7=32-6x 
   7x+6x=39 
   13x=39⇒ x=3
4. 7/3-4x=3/5
    4x=7/3 -3/5 aducem la ac numitor care este 15
   60x=35-9
   60x=26⇒ x=26/60=13/30
5.2(x+1)-7(x-3)=3(x+10)+1
   2x+2-7x+21=3x+30+1
   23- 5x=3x+31
   23-31=3x+5x
   -8=8x⇒ x= - 1
6.  \frac{x-2}{6} - \frac{2x+13}{8} = \frac{37}{24} - \frac{12+x}{4}
Aducem la ac numitor care este 24
4(x-2)-3(2x+13)=37-6(12+x)
4x-8-6x-39=37-72-6x
4x-6x+6x=-35+39+8
4x=12⇒ x=12:4=3
7. 3(x-1)-6=2(x+7)
    3x-3-6=2x+14
    3x-9=2x+14
    3x-2x=14+9
    x=23